Implementation of Problem Based Learning Model in Improving Elementary School Students' Mathematics Learning Outcomes - Wiastrini, Ni Wayan Eka; Suranata, Kadek; Trisna, Gusti Ayu Putu Sukma (Mimbar Ilmu, 2024)
Mathematics learning in elementary schools is intended so that students can master basic Mathematics knowledge and concepts in it and are skilled in applying it to real life. Facts in the field show that many students still have low Mathematics learning outcomes. This study aims to analyze the effect of the problem based learning model on the Mathematics learning outcomes of fifth grade elementary school students. The research design used is Quasi Experimental Research with the type of Non Equivalent Control Group Pre-test Post-test Design. The population in this study was 144 fifth grade elementary school students spread across nine schools. Sampling in this study used the Cluster Random Sampling technique with 16 students as the experimental group and 22 students as the control group. The technique of collecting Mathematics learning outcome data was carried out using a multiple-choice test consisting of 20 questions. Furthermore, the data was analyzed using the t-test. The results obtained were t count = 8.14 and ttable = 1.69. The test criteria showed tcount (8.24) > ttable (0.69) so H1 was accepted and H0 was rejected. This indicates that there is a significant influence of the problem-based learning model on the Mathematics learning outcomes of fifth-grade elementary school students. The latest information in the study has implications for its use as a reference for teachers to improve learning so that students' Mathematics learning outcomes are as expected.